RESEARCHING THE EFFECT OF FOOTBALL IN DISTRIBUTION OF SOLE PRESSURE IN FEMALE FOOTBALL PLAYERS - Uzun Ahmet; Aydos Latif; Kaya Metin; Kanatli Ulunay; Esen Erdinc (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2014)
Purpose: The purpose of this research is to research the effect of football on sole comparing the peak pressure, average maximal pressure and pressure-time integral pedobarographic parameters of 11 contact areas of soles of professional female football players and healthy individuals. Working Plan: 22 female football players (18,80 ± 2,2 age) and 28 female volunteers (27,5 ±6,6 age) (as the control group) having no foot complaints were included in the study. In the research EMED-SF (Novel GmbH, Munich, Germany) plantar pressure analysis system was used. It was examined whether there was any statistically significant difference between the experiment and control group means using non-parametric Mann Whitney U test, the size of the linear relation between physical structure and variables of sole was examined by calculating Pearson's (r) coefficient. In the measurements 95% reliability range and P < 0.01 - 0.05 were accepted as meaningfulness level. Findings: At the end of the measurements, it was found that there were meaningful differences between the female football players and control group in right foot 2 left feet 1st, 2nd, 3rd, 4th metatarsal heads sole 11 contact areas peak pressure and in the 3rd, 4th and 5th toes, at average maximal pressure in right and left foot in 2nd metatarsal heads and time pressure integral in right foot 2nd and 3rd metatarsal heads and left foot heel medial, heel lateral, 2nd, 3rd and 4th metatarsal heads. Arguments: In our findings, it was found that the pressure in football players' sole front interior regions was higher than both the control group and the other regions in their own feet. It was determined that the particularly the crampons used by the football players were insufficient to protect the sole and failed to prevent permanent sole pressure parameters. As a result, Football players' excessive pressing against their soles in forcing movements in long term exercises and matches are indicated to cause change in the sportsmen's sole pressure regions and values.